Measuring physical literacy for an evidence-based approach: Validation of the French perceived physical literacy instrument for emerging adults - Joseph Gandrieau; Olivier Dieu; François Potdevin; Thibaut Derigny; Christophe Schnitzler (Elsevier, 2023)
Background/Objectives: Physical Literacy (PL) is increasingly recognized as a key element in studies aimed at promoting Physical Activity (PA), but measurement tools for emerging adults and evidence for assessing and using this concept is lacking in a wide range of contexts. We aimed to validate the French version of the Perceived Physical Literacy Instrument (PPLI): a scale for investigating PL in young French adults. Methods: After PL and PA data collection (n = 2,248, agemean = 19 ± 1.53 yrs), exploratory and confirmatory factor analyses, Cronbach's α and Omega's ω and an Intraclass-Correlation analysis were undertaken. Spearman's rank correlation and the Boruta algorithm were used to investigate the association between PL and PA. Boruta's algorithm examined deeper external validation by analyzing the strength of an overall PL score in explaining PA, compared with separate dimensions of PL and individual characteristics (BMI, sex). Results: Results showed an acceptable level of reliability (ICC = 0.91), internal validity (α = 0.88; ω = 0.77), and external validity (Rhô >0.18, p < 0.01). The Boruta algorithm highlighted that the construct of PL is a significant predictor of PA, although not the strongest one which is social and affective dimension. Conclusion: This study provided data on validity and reliability of the first French assessment tool to measure PL constituted by four intertwined dimensions (physical, cognitive, social, affective). At the same time, it provides new evidence of the association between PL and PA.